Levirate marriage and HIV and AIDS in Zimabwe: the story of Judah and Tamar (Genesis 38) - Mbuwayesango, Dora R. (Journal of Constructive Theology, 2007)
Explores how the biblical narrative is used to promote the tradition le levirate marriage in Zimbabwe.